2006
DOI: 10.1089/jpm.2006.9.855
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Utilization Outcomes of Patients Receiving Hospital-Based Palliative Care Consultation

Abstract: PC was associated with significantly lower likelihood of ICU use and lower inpatient costs compared to UC. Our findings coupled with those indicating better patient and family outcomes with PC suggest both a cost and quality incentive for hospitals to develop PC programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
191
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 251 publications
(205 citation statements)
references
References 37 publications
8
191
4
2
Order By: Relevance
“…Observational designs dominate with 9 cohort studies [23][24][25][26][28][29][30][31]33 and 1 randomized controlled trial. 27 Among observational studies there is a wide variation in size with 5 having intervention groups of between 27 and 164 patients, [23][24][25][26]28 and 1 study having 4908 intervention patients. 29 Nine of the studies restrict their perspective to the hospital and do not evaluate patient or caregiver outcomes.…”
Section: Design and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational designs dominate with 9 cohort studies [23][24][25][26][28][29][30][31]33 and 1 randomized controlled trial. 27 Among observational studies there is a wide variation in size with 5 having intervention groups of between 27 and 164 patients, [23][24][25][26]28 and 1 study having 4908 intervention patients. 29 Nine of the studies restrict their perspective to the hospital and do not evaluate patient or caregiver outcomes.…”
Section: Design and Approachmentioning
confidence: 99%
“…29 Nine of the studies restrict their perspective to the hospital and do not evaluate patient or caregiver outcomes. [23][24][25][26][28][29][30][31]33 The remaining article analyzes total health care costs for 6 months postdischarge as well as some patient outcome measures but does not quantify the relationship between the two. 27 While there is variation in terms of hospital type and the label given to multidisciplinary teams, the composition of those teams are broadly consistent.…”
Section: Design and Approachmentioning
confidence: 99%
“…10,[23][24][25][26][27][28][29][30][31] Increased median longevity was observed among patients with small-cell lung cancer in early referral outpatient palliative care settings versus usual care. 32 Patients provided with inpatient palliative care consults were less likely to die in intensive care units and more likely to receive hospice referrals.…”
Section: Palliative Care Interventions Designed To Meet Needs Of Patimentioning
confidence: 99%
“…(20)(21)(22)(23)(24) Additionally, a recent study has also shown that receipt of hospital-based palliative care services is associated with significantly lower likelihood of admission to an ICU and lower inpatient costs. (25) Therefore, available data suggests that high-quality palliative care leads to both improved patient-and family-centered outcomes and decreased costs. It is the intent of this review to highlight the major factors involved in providing palliative and end-of-life care to older patients with lung diseases.…”
Section: Introductionmentioning
confidence: 99%